A Content Analysis of Patient Advocacy Organization Policies Addressing Institutional Conflicts of Interest. Issue 4 (2nd October 2019) - Brems, John H.; McCoy, Matthew S.
Abstract: Introduction: Patient advocacy organizations (PAOs) provide patient education, raise public awareness, and influence health policy for a wide range of diseases. These organizations frequently receive financial support form from drug, device, and biotechnology companies. Though PAOs often develop policies to address institutional conflicts of interest arising from industry relations, little is known about the substance of these policies.Methods: We sampled all PAOs that are members of the National Health Council. Using a standardized search strategy, all policies were obtained from each organization if publicly available. We reviewed policies for content related to restrictions on corporate partnerships, disclosure of corporate funding, and governance and monitoring of corporate partnerships.Results: We found that 24 of 47 (51%) organizations had policies that addressed institutional conflict of interest. A total of 9 of those 24 (38%) policies placed any restriction on the types of corporations that the PAO would or would not partner with. While 16 of the 24 (67%) outlined some process for disclosure of the organization's corporate donors, only 5 of 24 (21%) specified a manner for disclosing the financial value of those donations. Further, 15 of the 24 (63%) policies identified the person or persons responsible for approving corporate partnerships. However, 17 (71%) failed to address or specify the person(s) responsible for ongoing review of those partnerships.Conclusion: Nearly half of the organizations studied did not have publicly available conflict of interest policies. Among those that did, few policies had a substantial level of detail or limitations to guard against conflicts of interest.